Determination of Urinary Neutrophil Gelatinase-Associated Lipocalin (uNGAL) Reference Intervals in Healthy Adult and Pediatric Individuals Using a Particle-Enhanced Turbidimetric Immunoassay - Tabari M. Baker; Christopher A. Bird; Dennis L. Broyles; Ursula Klause (Diagnostics)
Background: The current gold standards for diagnosing acute kidney injury (AKI) are an increase in serum creatinine and a decrease in urine output, which are inadequate for rapid diagnosis. Neutrophil gelatinase-associated lipocalin (NGAL) is a 25-kDa protein produced and secreted by injured kidney tubule epithelial cells, and can serve as an early urinary biomarker for AKI. ProNephro AKI (NGAL) is an immunoassay for the quantitative determination of NGAL in urine (uNGAL) that recently received FDA clearance. A multisite, cross-sectional study was conducted to establish reference intervals for uNGAL in apparently healthy individuals. Methods: Urine samples were collected from apparently healthy individuals aged ≥3 months who met all inclusion criteria and no exclusion criteria. Specimens were temporarily stored at room temperature or 2–8 °C, then transferred into urinalysis tubes before being frozen and shipped for testing. uNGAL testing was performed using the ProNephro AKI (NGAL) immunoassay on a Roche cobas c501 analyzer. Results: Of the 688 individuals screened, 677 were eligible, and 629 (91.4%) of those were deemed evaluable. The 95th and 97.5th percentile uNGAL values for all pediatric participants were below the clinical cutoff of 125 ng/mL. uNGAL values were statistically significantly higher for female vs. male participants in both adult (p = 0.003) and pediatric groups (p < 0.001), while differences were not statistically significant for age, site location, race, or ethnicity. Conclusions: This study provides normal reference intervals for uNGAL with the ProNephro AKI (NGAL) clinical chemistry immunoassay that may be useful for interpreting patient results.